O lúdico e o esporte, o analógico e o digital: a reconfiguração das aulas de educação física - Sousa, Jeferson Coutinho de (Universidade do Vale do Rio dos Sinos, 2020)
This study aimed, based on action research, to propose a reconfiguration in physical education classes, based on new elements for motivation and engagement and variation between recreational and sports activities, analogical and digital devices, individual and collectives, that provide improvements in the teaching and learning process. This comprehensive study was completed with the participation of forty individual students, all female, from a Jesuit Education Network School. As instruments, the BREQ-2, IPAQ (short version) and journal tools of measurement were used. The identification motivation reveals that the participants during morning period were considered less autonomous and self-determined for physical activity practice, while those during the afternoon more autonomous and self-determined as regulation for physical activity practice more identified and intrinsic, coming through physical education class profiles. For physical activity practice level identification, it was found that the participants during morning classes 75% were observed “Active”, 16.7% “A Active Insufficiently” and 8.3% “B Active Insufficiently” while afternoon classes 100% were considered “Active”. Regarding the view of the proposed reconfiguration, variation, comparison and transformation of analogical activities in the participants positions, there was an evaluation of the morning classes to be of 50% for a “very good”, 29.2% for “good” and 20.8% for “reasonable” classes, albeit, it was observed in afternoon classes an assessment of 62.5% for a “good”, 25% for “reasonable” and 12% for “very good” classes. Activities involving digital devices it was observed an evaluation in the morning classes to be of 46% for a “good”, 29% for “very good”, 17% for a “reasonable” and 8% for “very bad” classes while for afternoon classes to be 69% for a “good” and 31% to “reasonable” class. This study would conclude with associated measurements techniques, that the participants positioning corroborates to class profile, similarly to afternoon classes which has being motivated and engaged while morning classes were less motivated and less engaged for physical activities practice in physical education classes. According to the student´s desires, the morning and afternoon classes favored and exhibited a preference for more physical education classes, in interchangeable spaces, with more challenges, materials and in an interactive way, which provides important information for making decisions to the researched school management.
Keywords: Gestão de educação básica; Educação física; Motivação; Tecnologia; Basic education management; Physical education; Motivation; Technology; ACCNPQ::Ciências Humanas::Educação